Factorise and Expand

Algebra Level 2

Find the value of ( x + 1 ) ( x 1 ) 2 (x + 1) (x - 1)^2 , given that x 5 x 4 = x 4 x x^5 - x^4 = x^4 - x and x 0 , 1 x \ne 0, 1 .

2 2 0 0 x x 1 1 3 3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 28, 2020

Given that:

x 5 x 4 = x 4 x Since x 0 , we can divide x 4 x 3 = x 3 1 both sides by x . x 3 ( x 1 ) = ( x 1 ) ( x 2 + x + 1 ) Since x 1 , we can divide x 3 = x 2 + x + 1 both sides by x 1. \begin{aligned} x^5 - x^4 & = x^4 - x & \small \blue{\text{Since }x \ne 0 \text{, we can divide}} \\ x^4 - x^3 & = x^3 - 1 & \small \blue{\text{both sides by }x.} \\ x^3(x-1) & = (x-1)(x^2 + x + 1) & \small \blue{\text{Since }x \ne 1 \text{, we can divide}} \\ x^3 & = x^2 + x + 1 & \small \blue{\text{both sides by }x-1.} \end{aligned}

x 3 x 2 x = 1 \implies \red{x^3 - x^2 - x = 1}

Now we have ( x + 1 ) ( x 1 ) 2 = ( x 2 1 ) ( x 1 ) = x 3 x 2 x + 1 = 1 + 1 = 2 (x+1)(x-1)^2 = (x^2-1)(x-1) = \red{x^3 - x^2 - x} + 1 = \red 1 + 1 = \boxed 2 .

x 5 x 4 = x 4 x x 3 x 2 x = 1 x 3 x 2 x + 1 = 2 ( x + 1 ) ( x 2 2 x + 1 ) = 2 ( x + 1 ) ( x 1 ) 2 = 2 x^5-x^4=x^4-x\implies x^3-x^2-x=1\implies x^3-x^2-x+1=2\implies (x+1)(x^2-2x+1)=2\implies (x+1)(x-1)^2=\boxed 2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...